2008
DOI: 10.2166/wst.2008.242
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reclaimed wastewater on the quality and growth of grapevines

Abstract: The effect of the use of treated wastewater on the growth of cabernet sauvignon and merlot grapes from the Guadalupe Valley, Mexico was evaluated. Secondary advanced effluent was used to irrigate the grapevines at a rate of 66 L/vine/week. Wastewater quality results confirmed that all parameters complied with Mexican legislation for crop irrigation as well as reuse in activities in which the public would be in direct or indirect contact with the reclaimed water. Results showed that the number of leaves per sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 2 publications
3
22
0
1
Order By: Relevance
“…They concluded that drip irrigation systems are preferred to achieve several small irrigations per day in order to avoid deep percolation losses. Mendoza-Espinosa et al [3] evaluated the effect of treated wastewater on the growth of cabernet sauvignon and merlot grapes from the Guadalupe Valley, Mexico. They reported that the number of leaves per shoot and the overall biomass increased in plants irrigated with wastewater and grape production per plant was 20% higher and the concentration of carbohydrates, organic acids and pH were similar in grapes from vines irrigated with wastewater to those irrigated with groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that drip irrigation systems are preferred to achieve several small irrigations per day in order to avoid deep percolation losses. Mendoza-Espinosa et al [3] evaluated the effect of treated wastewater on the growth of cabernet sauvignon and merlot grapes from the Guadalupe Valley, Mexico. They reported that the number of leaves per shoot and the overall biomass increased in plants irrigated with wastewater and grape production per plant was 20% higher and the concentration of carbohydrates, organic acids and pH were similar in grapes from vines irrigated with wastewater to those irrigated with groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater from the nearby aquifers is the main source for Maneadero and Guadalupe irrigation. From 28 to 32 Mm 3 /yr of water are extracted from the Guadalupe aquifer, supplying roughly one third for potable water supply for the city of Ensenada and twothirds for agriculture in the Guadalupe valley, which supports the most important wineries in the country (Daesslé et al, 2006;Mendoza-Espinosa et al, 2008). Despite the economic importance of agriculture in these three areas, urban uses continue to expand.…”
Section: Agricultural Water Demand Modelmentioning
confidence: 99%
“…This trial has been applied in Haram City farm (HCF) to evaluate the reuse of treated wastewater in agricultural sectors, its effect on soil properties and fish farming. Mendoza [3] assessed the influence of treated wastewater (TWW) on merlot grapes and the growth of cabernet sauvignon from Guadalupe Valley, Mexico. He stated that the leaves number/ shoot and the whole biomass improved in plants irrigated with TWW and production/plant of grape was higher by twenty percent.…”
Section: Introductionmentioning
confidence: 99%